Barang Kebutuhan Pokok Dan Jasa-Jasa Tertentu Menjadi Barang Dan Jasa Kena Pajak Di Dalam UU HPP: Meninjau Penyebab Dan Dampak - Khaista Muftiha Siregar; Muhammad Taufiq Budiarto (Politeknik Keuangan Negara STAN, 2022)
Law Number 7 of 2021 or the Law on the Harmonization of Tax Regulations states that basic goods and certain services are classified as taxable goods and services that receive exemption from VAT facilities which were previously classified as nonobjects in Law Number 42 of 2009. The purpose of writing this final task paper is to find out the causes of changes in the grouping of basic goods and certain services and the impact of these changes in grouping. The data collection methods used are interviews and literature study. The results of the study indicate that the causes of changes in the grouping of basic goods and certain services include as a step to support the availability of certain strategic goods and services in the context of social development and the need for fair and targeted policies as a response to the impact of the Covid19 pandemic that taking place in Indonesia. The impacts that occur as a result of changes in the grouping of basic goods and certain services include input tax from the acquisition of supporting goods and services to produce basic goods and certain services can be credited by taxable employers and the emergence of tax obligations by entrepreneurs engaged in certain basic goods and services which have a gross income exceeding Rp.4.8 billion.